The current Ebola outbreak: old and new contexts - Saverio Bellizzi (Journal of Infection in Developing Countries)
Within the ongoing Ebola outbreak in West Africa, separate scenarios reflect old contexts with well-known strategies to face the epidemic on one side and completely new and unprecedented situations requiring new approaches on the other side. While Senegal and Nigeria represent success stories on the implementation of appropriate standard public health measures for containment, Liberia, Sierra Leone, and Guinea require a major and innovative scale of actions to halt even more catastrophic consequences.